A Modulated Double‐Passivation Strategy Toward Highly Efficient Perovskite Solar Cells with Efficiency Over 21%. Issue 12 (4th September 2019) - Dong, Hang; Yue, Man; Pang, Shangzheng; Zhu, Weidong; Chen, Dazheng; Xi, He; Lin, Zhenhua; Chang, Jingjing; Zhang, Jincheng; Hao, Yue; Zhang, Chunfu
Abstract : Material passivation is essential to enhance the quality of perovskite materials and boost the performance of perovskite solar cells (PSCs). However, most of the previous reports only paid attention to improving the quality of perovskite films by adopting single passivation. Here, a facile strategy that can carry out double passivation to improve the performance of PSCs is demonstrated. By using the dilute halide salt PEABr solution to treat the perovskite film, PbI2 can precipitate from the perovskite. Both PEABr and PbI2 can passivate the perovskite film, and by combining PEABr and PbI2, the double passivation improves the performance of PSCs significantly. Very high short‐circuit current density of 24.30 mA cm −2, open‐circuit voltage of 1.10 V, and fill factor of 79.75% are achieved which lead to a surprising efficiency of 21.32% for the passivated device. The improved efficiency is mainly according to the available surface passivation of the perovskite material, leading to repressed nonradiative recombination and unhindered charge collection. In addition, the passivated device exhibits better power conversion efficiency stability relative to the control device. Abstract : Herein, a facile strategy that can carry out double passivation to improve the performance of perovskite solar cells (PSCs) is demonstrated. By using the dilute halide salt PEABr solution to treat the perovskite film, PbI2 can precipitate from the perovskite. Both PEABr and PbI2 can passivate the perovskite film; double passivation improves the performance of PSCs significantly.